From Community-Based Rehabilitation (CBR) Services to Inclusive Development. A Study on Practice, Challenges, and Future Prospects of CBR in Gedeo Zone (Southern Ethiopia) - Ayalew, Ababu T.; Adane, Dejene T.; Obolla, Solomon S.; Ludago, Tesfaye B.; Sona, Berhanu D.; Biewer, Gottfried (Frontiers in Education, 2020)
The purpose of this article is to explain the practice, challenges and future prospects of community-based rehabilitation (CBR) in Gedeo zone, a district of nearly one million inhabitants in the south of Ethiopia. The study used a mixed methods design. The quantitative part of the study involved 138 parents and care givers selected by convenient sampling technique. In addition, a total of 22 (seven female and 15 male) research participants were purposively selected from various categories: one head of zone labor and social affairs, three heads of district labor and social affairs, three representatives of associations of PWDs, 11 parents, two CBR heads, and two CBR social workers. Questionnaires and interviews were used as tools of data collection. The data were analyzed using both descriptive and thematic analysis. The finding indicated that there was no well-established CBR service provision for PWDs in Gedeo zone to ensure full participation and successful adjustment in the community. The article also revealed that a lack of trained manpower, following the charity model of CBR, and a failure to understand the modern essence of CBR were some of the major challenges that hindered the implementation of CBR service in Gedeo zone. Based on the findings, we recommend the establishment of rehabilitation centers in combination with community services in various districts of the zone. Community-based rehabilitation requires centers with skilled staff, able to empower local people in the community to develop inclusive structures. Furthermore, we suggest that the practice of CBR in Gedeo zone should empower CBR workers in community-based inclusive development.